Optimizing Acute Pain Management After Trauma in the Emergency Department: the Role of Regional Nerve Blocks by Anesthesiologists: A Literature Review - Agastya, Wayan Dhea; Rahmadinie, Amalia (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
Abstract Background: Acute pain management remains a critical challenge in emergency departments (EDs), particularly in trauma cases. Traditional systemic analgesics, especially opioids, pose risks of adverse effects and dependency. Regional nerve blocks (RNBs), administered by anesthesiologists, offer a promising alternative. This literature review explores the efficacy, safety, and practical considerations of RNBs in trauma-related acute pain within ED settings. Evidence suggests that RNBs significantly reduce pain scores and opioid consumption while maintaining a favorable safety profile. Collaborative implementation of RNBs in EDs can improve patient outcomes and reduce opioid-related risks. Method: This research employs a literature analysis approach by reviewing relevant theoretical and empirical sources, including Google Scholar, PubMed, and ScienceDirect. Discussion: The findings reveal that RNBs, particularly when guided by ultrasound and performed by anesthesiologists, significantly reduce pain scores, opioid use, and side effects compared to systemic analgesia. Despite logistical barriers in ED settings, collaborative approaches between emergency physicians and anesthesiologists enhance feasibility and patient outcomes. Conclusion: Regional nerve blocks by anesthesiologists offer fast, targeted, and safer pain relief in trauma care, reducing opioid dependence and improving outcomes. Integrating RNBs into emergency protocols enhances patient care and should be prioritized. Keywords: Regional Nerve Block, Trauma Pain, Emergency Department, Anesthesiologist